2015
DOI: 10.1016/j.nimb.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide transfer efficiency and lethal load in Argentine ants

Abstract: Trophallaxis between individual worker ants and the toxicant load in dead and live Argentine ants (Linepithema humile) in colonies exposed to fipronil and hydramethylnon experimental baits were examined using accelerator mass spectrometry (AMS). About 50% of the content of the crop containing trace levels of 14C-sucrose, 14C-hydramethylnon, and 14C-fipronil was shared between single donor and recipient ants. Dead workers and queens contained significantly more hydramethylnon (122.7 and 22.4 amol/μg ant, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Lack of direct exposure combined with reduced susceptibility and extreme polygyny may allow the queens to survive insecticide treatments and lead to quick regeneration of worker ants. Previous studies have suggested that the resurgence of polygynous ant colonies treated with baits may be explained by queen survival resulting from sublethal doses due to a slowing of trophallaxis throughout the colony (Hooper-Bui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of direct exposure combined with reduced susceptibility and extreme polygyny may allow the queens to survive insecticide treatments and lead to quick regeneration of worker ants. Previous studies have suggested that the resurgence of polygynous ant colonies treated with baits may be explained by queen survival resulting from sublethal doses due to a slowing of trophallaxis throughout the colony (Hooper-Bui et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some methods, such as biocontrol agents or application of toxic bait products containing slow‐ or fast‐acting insecticides have been widely used or shown potential for the control of S. invicta (Williams et al ., ; Oi & Oi, ; Kafle et al ., ; McNaught et al ., ; Wylie et al ., ). These methods largely depend on the effective foraging and ingestion of toxic baits followed by horizontal transfer of active ingredients among ant nestmates through trophallaxis (Oi & Oi, ; Hooper‐Bùi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Invasive alien species have caused serious negative effects on agriculture, human health, native ecosystems, and biodiversity 1–3 . Among them, the red fire ant, Solenopsis invicta Buren (Hymenopter: Formicidae), originating from South America, is the most serious invasive ant species 4 .…”
Section: Introductionmentioning
confidence: 99%